Problems Faced by the Students at Grade Eight of SMPN 14 Palu in Reading Recount Text: Masalah yang Dihadapi Siswa Kelas Delapan di Smpn 14 Palu dalam Membaca Recount Teks - Sitti Hadijah; Nur Sehang Thamrin; Ernitasari Mulyadi (Universitas Muhammadiyah Palu, 2022)
The purpose of this research is to investigate the reading recount text problems faced by grade eight students of SMPN 14 Palu. In this research applied descriptive design. The research subject was grade eight students of SMPN 14 Palu. The number was 24 students taken from eight classes by using random sampling technique. The data of the research were collected by carrying out the interview, test, qustionnaire and observation activities. The result of this research indicate that students lack of vocabulary, students find it difficulty to determine main idea in reading text and students find it difficulty to pronounce words when reading texts.